(untitled) (Journal of Medicine, 2014)
Autoimmune polyendocrine syndrome type 1 (APS-1) is a rare autosomal recessive disorder characterized by autoimmune multiorgan dysfunction. The major components of APS type 1 are chronic mucocutaneous candidiasis,hypoparathyroidism and Addisons disease.To establish this syndrome, at least two of these conditions have to be present. We report here one of such case, a 15-year old boy who presented with features of chronic mucocutaneous candidiasis, hypoparathyroidism, primary hypothyroidism,nail dystrophy and dental enamel hypoplasia that were consistent with APS-1. DOI: http://dx.doi.org/10.3329/jom.v15i1.19886 J Medicine 2014; 15: 98-101